A Framework for 21st-Century Career-Technical and Workforce Education Curricula. Issue 2 (15th March 2017) - Rojewski, Jay W.; Hill, Roger B.
Abstract : Increasingly, career-technical and workforce education professionals are challenged with determining the best ways to prepare people for work, when many of the jobs those people will perform do not exist yet. Twenty-first-century work is evolving rapidly, with some jobs going away, other types of work appearing, and many people working in jobs that do not maximize their potential. To remain relevant in this emerging landscape, a framework is needed that can structure and guide research and curriculum development in workforce preparation in an increasingly volatile and uncertain future. We examine three key components—career navigation, work ethic, and innovation—that can situate career-technical and workforce education curricula to anticipate rapid changes in workplace demands and ensure student outcomes that will be lasting and durable in the 21st-century workplace.